Comparison of Career Maturity of Students from a Gender Perspective - Titik Wiyul Fitrhi; Nurfahanah Nurfahanah; Yeni Karneli; Zadrian Ardi (HUMANISMA : Journal of Gender Studies, 2026)
This research is motivated by the phenomenon of differences in social roles and gender expectations that have the potential to influence students' career planning and decision-making. This study aims to analyze differences in the level of career maturity of students reviewed from a gender perspective in UIN Sjech M. Djamil Djambek Bukittinggi. The novelty of this research lies in strengthening the study of gender-based career maturity in the context of students at state Islamic universities. This research method is comparative quantitative with analysis techniques of normality test, homogeneity test and independent test. The research subjects were 84 male students and 84 female students selected using convenience sampling technique . The research instrument used a career maturity scale that has been tested for validity and reliability. The results showed that there was no significant difference between the career maturity of male and female students, visually the data showed a slight difference in the aspect of career exploration where female students tended to be more proactive. This finding indicates the importance of gender-responsive career guidance services in the higher education environment.